The Motif of ‘Imaginary Travel’ in Panoramic Spectacles of the First Half of the 19th Century in Russia - Novik, Alina (Actual Problems of Theory and History of Art, 2018)
The article describes the history of the exhibition and reception of panoramas and related spectacles in St. Petersburg and Moscow in the first half of the 19th century. Their most popular subject was a so-called ‘imaginary travel’ to distant corners of the globe. Quite often, visits to such exhibitions were the only opportunity for the average citizen to witness other geographical destinations. In spite of the huge number of academic works on this internationally widespread ‘travel-replacement’ entertainment of the 19th century, Russian material remains practically unexplored. The research concentrates on the motif of ‘imaginary travel’ in circular and moving panoramas; cosmoramas, and georamas; as well as the peculiar properties of its incarnation by the technical means of these four media.The fluctuations in the subject were partially determined by the difference of the technological nature of various panoramic spectacles. A circular panorama created an illusion of total immersion into the pictorial reality and was suitable for the depiction of a particular sight. A cosmorama was an exhibition, which consisted of several peepshows and used the motif of ‘imaginary travel’ around the world (or through its particular region). A ribbon-shaped moving panorama was best suited for the image of long extensive travels including those by railway and river transport. Finally, a spherical georama allowed drawing up the most complete picture of the different parts of the globe in relation to each other. Referring to the periodicals of the mentioned period, the author attempts to restore the Russian reception of the circular panorama of Paris by H. R. Philastre and C.-A. Cambon, the cosmorama of C. Suhr, the moving panorama of Mississippi river by the unknown author, and the georama arranged in St. Petersburg by E. A. Le Molt. The analysis of the majority of the materials on the history of this phenomenon in Russia has been published for the first time.
Keywords: imaginary travel; panoramic spectacles; circular panorama; cosmorama; moving panorama; optical spectacles; visual culture; 19th-century Russia